Tumor-Like Mass in Patient with Tuberculosis : Is It Really a Malignancy? a Case Report - Joshua Kurniawan; Annisa Ananda; Kasum Supriadi (Universitas Malahayati Lampung, 2023)
ABSTRACT Tuberculosis (TB) is not all about chronic cough or hemoptysis. The clinical manifestation of TB could be pulmonary and extrapulmonary, with the later defined as any site other than the lung, affected by the TB. The global burden for tuberculosis is still heavy, standing as the second leading infectious killer after COVID-19 (above HIV/AIDS), TB holds the 13th place of the leading cause of death. The World Health Organization (WHO) predicted around 1.6 million people died from TB, and 10.6 million people fell ill with TB worldwide in 2021. Due to the various manifestations and limitations of the diagnostic tools, determining the diagnosis and treatment of TB has always been a challenge since a long time ago. To give appropriate therapy, making an accurate diagnosis is crucial. It is known that extrapulmonary tuberculosis manifestation often mimics malignancy, both clinically and radiologically. The treatment for these cases should include treatment for the infection and the affected organ or site, following the recommended therapy dose and duration. Neurological examination should be evaluated, especially for tuberculosis of the spine. Surgical approach should be considered for cases with neurological deficits, patient with spine-at-risk, progressive spinal deformity, severe pain, spinal instability, or uncertain diagnosis. Physical therapy could be considered to improve respiratory function, improving muscle strength, reducing the pain, repair/improve the range of motion, sensory function, improve quality of life, and prevent other complications. Keywords: Extrapulmonary Manifestation, Mimics Malignancy, Tuberculosis